STRATEGI PENGEMBANGAN WISATA DI KAWASAN GUNUNG ANDONG MAGELANG - M. Ryan Saputra; Rodhiyah Rodhiyah (Jurnal Ilmu Administrasi Bisnis, 2016)
Tourism industry is one of the national income sources that playing an importantrole to improve the prosperity of local communities. Mt Andong as one of tourismdestination in Central Java still lose in term of number of visitors when compare to anothertourism destionation in Central Java. Based on presurvei result that being conducted bywriter, the problem was caused by the lack of goverment asistance, the lack of publictransportation to access the tourism destination, traffic condition with minimum road light,and unpredictable nature phenomenons. Tourism development strategy was required tomaximize the benefit, and less the issue of tourism destination development effort.This study was conducted to figure out the internal and external factor that wouldbecome strengths and weaknesses, alongside as opportunities and threats in thedevelopment of the Mt. Andong tourism area. This study is a descriptive qualitative studyby using in-depth interviews, observation techniques, and documentation as the datacollection methods. Then the finding was analyzed by using SWOT method. Based on theSWOT analysis, some strategies that can be applied to develop the tourism area aredevelop new tourist attractions such as agricultural tourism, establish tour guides group,porters and enhance outdoor equipment rental services, use the tourist visa-free policy toattract foreign tourists, and held a folklore festival as variation for tourist attraction.